THE CHALLENGE OF EDUCATION AND LEARNING IN THE DEVELOPING WORLD - Gowher Hassan (RADJA PUBLIKA, 2023)
In the context of the developing world, this study addresses the critical issue of education and learning challenges. The problem under examination pertains to the complex interplay of factors affecting school participation and learning outcomes. Specifically, the study focuses on the sensitivity of school attendance to financial considerations, the efficacy of interventions aimed at increasing enrollment, and the persistently low and unresponsive test scores among enrolled students. The scope of this research encompasses various contexts and interventions, ranging from reducing out-of-pocket costs and providing scholarships to incorporating conditional cash transfers. Additionally, the study delves into efforts to enhance child health and furnish information regarding the benefits of education on income growth. The effectiveness of different strategies, such as pedagogical reforms tailored to students' learning levels and accountability-improving measures, is examined comprehensively. Technological advancements and their potential to revolutionize pedagogy and accountability are also explored within the context of education in the developing world. The study acknowledges that the challenges extend beyond the classroom, and consequently, emphasizes the need to enhance both pre-primary and primary education systems. By analyzing these multifaceted challenges and potential solutions, this research contributes to a deeper understanding of the education and learning landscape in the developing world, providing insights that can inform policy decisions and interventions aimed at improving educational outcomes.